A Review on Palm Vein Biometrics - Kavitha, S; Sripriya, P (International Journal of Engineering and Technology, 2018)
The technology of biometrics is a growing arena and it still needs to be explored related to each and every physical and biological features of human. The recent trends in embedded technology and other areas has bloomed the biometric techniques to greater heights. Vein biometrics has its own advantages and disadvantages.  The advantage is that the veins are present internally inside the body and cannot be forged easily. The paper presents the literature survey a review on palm vein biometrics.